2022
DOI: 10.1111/jdv.18132
|View full text |Cite
|
Sign up to set email alerts
|

Haemorrhagic bullous pyoderma gangrenosum following COVID‐19 vaccination

Abstract: induces readily detectable morphologic and inflammation-related phenotypic changes in peripheral blood monocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…There have been several studies reporting skin adverse events after COVID-19 vaccination, including PG [30][31][32][33][34]. This is not the case in our patient since her last COVID-19 vaccination was one year prior to her disease relapse.…”
Section: Discussionmentioning
confidence: 54%
“…There have been several studies reporting skin adverse events after COVID-19 vaccination, including PG [30][31][32][33][34]. This is not the case in our patient since her last COVID-19 vaccination was one year prior to her disease relapse.…”
Section: Discussionmentioning
confidence: 54%
“…Several studies over the past 2 years have reported skin side-effects after COVID-19 vaccination, including PG. 17 – 21 To the best of our knowledge, a PG ulcer triggered by COVID-19 vaccination in a patient with UC has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Several cases of PG have been reported as a potential side-effect following SARS-CoV-2 vaccination. [2][3][4][5][6][7] In this case, the Naranjo Adverse Drug Reaction Probability Scale score was 9 out of 13, indicating a definite relationship between the vaccination and the recurrence of PG (Table 1). This association is further strengthened by the recurrence of PG after both doses of the vaccine.…”
mentioning
confidence: 84%